2012
DOI: 10.1371/journal.pone.0039516
|View full text |Cite
|
Sign up to set email alerts
|

Altered Cerebellar Functional Connectivity with Intrinsic Connectivity Networks in Adults with Major Depressive Disorder

Abstract: BackgroundNumerous studies have demonstrated the higher-order functions of the cerebellum, including emotion regulation and cognitive processing, and have indicated that the cerebellum should therefore be included in the pathophysiological models of major depressive disorder. The aim of this study was to compare the resting-state functional connectivity of the cerebellum in adults with major depression and healthy controls.MethodsTwenty adults with major depression and 20 gender-, age-, and education-matched c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
74
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(80 citation statements)
references
References 59 publications
6
74
0
Order By: Relevance
“…A recent quantitative meta-analysis of a considerable number of functional imaging studies of depressed patients revealed the abnormal activation of the ACC, the prefrontal cortex, the fusiform gyrus, and the temporal gyrus in depressed patients (Fitzgerald et al, 2008). In addition, the involvement of the cerebellum in MDD was confirmed by the findings of morphologic alterations and neural bias of the cerebellum in MDD studies during rest (Alalade et al, 2011;Liu et al, 2012;Zeng et al, 2012) and by task-related fMRI (Chantiluke et al, 2012;Fitzgerald et al, 2008). Although these findings have provided evidence for the dysfunction of the cerebellum in MDD, to our knowledge, the current study is the first to explore altered cerebellar-cerebral functional connectivity patterns to discriminate MDD patients from controls, which could provide a deeper understanding of the role of the cerebellum in the symptoms and deficits associated with MDD from the viewpoint of cerebellar-cerebral circuits.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A recent quantitative meta-analysis of a considerable number of functional imaging studies of depressed patients revealed the abnormal activation of the ACC, the prefrontal cortex, the fusiform gyrus, and the temporal gyrus in depressed patients (Fitzgerald et al, 2008). In addition, the involvement of the cerebellum in MDD was confirmed by the findings of morphologic alterations and neural bias of the cerebellum in MDD studies during rest (Alalade et al, 2011;Liu et al, 2012;Zeng et al, 2012) and by task-related fMRI (Chantiluke et al, 2012;Fitzgerald et al, 2008). Although these findings have provided evidence for the dysfunction of the cerebellum in MDD, to our knowledge, the current study is the first to explore altered cerebellar-cerebral functional connectivity patterns to discriminate MDD patients from controls, which could provide a deeper understanding of the role of the cerebellum in the symptoms and deficits associated with MDD from the viewpoint of cerebellar-cerebral circuits.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, the cerebellum has been shown to be involved in the pathology of depression by converging evidence. In addition to the structural abnormalities of the cerebellum observed in depression (Allen et al, 1997;Frodl et al, 2010;Lee et al, 2011;Liu et al, 2010;Peng et al, 2011;Soares and Mann, 1997), several functional MRI studies have found irregular activation patterns in the cerebellum, for instance, altered cerebellar-cerebral functional connectivity during the resting state (Alalade et al, 2011;Liu et al, 2012;Zeng et al, 2012) and abnormal cerebellum activation in MDD patients performing cognitive (Chantiluke et al, 2012) and emotional tasks (Fitzgerald et al, 2008;Frodl et al, 2010). Moreover, despite an early, intense dispute, the significant insight that the cerebellum not only subserves the prevailing motor coordination but also some other higher functions, i.e., cognition and emotion control, has achieved strong consensus (Allen et al, 1997;Gao et al, 1996;Konarski et al, 2005;Middleton and Strick, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Of note, cerebellar area IX has even been suggested to form a major node of this functional network (Habas et al 2009). Available investigations on altered cerebellar-cerebral functional connectivity in depressed patients have yet employed cerebellar seed regions other than area IX (Alalade et , Liu et al 2012, Guo et al 2013, Ma et al 2013. Also, the techniques for imaging data analyses in these investigations relied on conventional segmentation algoriths and did not employ cerebellum-optimized protocols (Guo et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, emerging evidence has indicated cerebellar abnormalities in MDD; specifically, smaller cerebellar and cerebellar vermal volumes have been found in MDD patients (Beyer and Krishnan, 2002;Shah et al, 1992). Neurobehavioral (Greer et al, 2005;Sweeney et al, 1998) and neuroimaging studies have associated MDD with abnormal cerebellar function (Kimbrell et al, 2002;Liu L. et al, 2012;Liu Z. et al, 2010;Nofzinger et al, 2005). Furthermore, previous findings have also shown cerebellar involvement in the stress response (Ito, 2006;Madtes and King, 1999;Mazzocchi et al, 1999;Sanchez et al, 2000).…”
mentioning
confidence: 99%